Respuestas
Respuesta dada por:
3
Sea la expresión:
![3x^{m+1} + 4x^{p + 1} =q x^{5} 3x^{m+1} + 4x^{p + 1} =q x^{5}](https://tex.z-dn.net/?f=+3x%5E%7Bm%2B1%7D++%2B++4x%5E%7Bp+%2B+1%7D+%3Dq+x%5E%7B5%7D+)
=>m +1 = p +1 = 5
m +1 = 5
m = 5 - 1
m = 4 y p = 4
=>q = 3 + 4
q = 7
Entonces:
m + p + q = 4 + 4 +7 = 15 Rtaaaaaaa
=>m +1 = p +1 = 5
m +1 = 5
m = 5 - 1
m = 4 y p = 4
=>q = 3 + 4
q = 7
Entonces:
m + p + q = 4 + 4 +7 = 15 Rtaaaaaaa
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años